RT-PCR method for selective detection of silent gene transcripts in silencing mutants in homothallic strains of Schizosaccharomyces pombe - Shakil Ahmed; Jagmohan Singh (BioTechniques)
Here we describe a method that allows selective detection of silent copy transcripts in homothallic strains of Schizosaccharomyces pombe in the presence of the active cassettes. The method involving RT-PCR (reverse transcriptase polymerase chain reaction) exploits our observation that the silent copy transcripts extend beyond the regions of homology to the flanking sequences specific for the donor cassettes, thus allowing design of oligos that are specific for the different donors. The results are validated using a known silencing mutant swi6.